Effect of some riveting process parameters on the fatigue life of double-shear lap joints. (April 2022) - Papuga, Jan; Stejskal, Jiří
Highlights: Effect of cladding and of anodizing on fatigue of riveted joints evaluated. Effect of drilling on fatigue of riveted joints evaluated. Effect of riveting on fatigue of riveted joints evaluated. Effect of friction between joined elements on fatigue of riveted joints evaluated. Abstract: Based on a motivating example, this review paper provides a survey of various parameters of a double-shear lap joint and of their effect on the fatigue life of such a joint. Because the common riveting characteristics that feature the size of the driven head and the residual stresses created are well known, the effects of cladding, anodizing, hole drilling, riveting, and coefficient of friction of adjacent surfaces are primarily evaluated. The results of various experiments in the gathered literature show that these secondary effects should not be simply neglected and that their research is still far from finished.